(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The main issues of energy saving and design of energy-saving technologies are presented for discussion. The current state of the art in this area, as well as promising developments are shown. The possibilities of alternative technologies are presented. The possibilities of creating devices based on superionic materials with prospects for use in alternative energy are also proposed.